Using apriori information in interferometric processing of high resolution sar data - V. A. Ushenkin; N. A. Egoshkin (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение, 2016)
The paper presents an analysis of approaches to using apriori information on relief to improve the quality of spaceborne SAR data interferometric processing. The impact of relief on geometric matching of SAR images is analyzed and an algorithm of fast and high-precision SAR image matching based on polynomial approximation of relief height impact is proposed. The necessity of perpendicular baseline refinement, given the current accuracy of navigation data, is shown. The need of using reference relief to refine the baseline is also shown. The expediency of baseline refinement before and after phase unwrapping is substantiated. The impact of the steepness of relief slope on the coherence estimation is calculated. The existing methods of phase unwrapping are analyzed and an algorithm of their combining is proposed, based on apriori information on each method. A criterion for selecting areas on the interferogram where the true phase varies greatly from pixel to pixel because of the steep relief slope is presented. Phase to - height conversion is also considered. Using publicly available global low resolution DEMs as apriori information on the relief is proposed.